Sepsis-induced changes in pyruvate metabolism: insights and potential therapeutic approaches - Louise Nuyttens; Jolien Vandewalle; Claude Libert (EMBO Molecular Medicine, 2024)
Abstract Sepsis is a heterogeneous syndrome resulting from a dysregulated host response to infection. It is considered as a global major health priority. Sepsis is characterized by significant metabolic perturbations, leading to increased circulating metabolites such as lactate. In mammals, pyruvate is the primary substrate for lactate production. It plays a critical role in metabolism by linking glycolysis, where it is produced, with the mitochondrial oxidative phosphorylation pathway, where it is oxidized. Here, we provide an overview of all cytosolic and mitochondrial enzymes involved in pyruvate metabolism and how their activities are disrupted in sepsis. Based on the available data, we also discuss potential therapeutic strategies targeting these pyruvate-related enzymes leading to enhanced survival.